Exploring teacher-initiated humour in Academic English classes: an Uzbek international university experience - Kholmatov, Aziz (European journal of humour research, 2021)
As a subject focused on teaching grammar forms needed for academic studies and genres of academic writing, Academic English may seem tedious at times. Sometimes it is a complex subject for students who are fresh to academia and it needs a peculiar didactic approach to provide a smooth transition of students from general to academic English writing at a university level. One of these approaches may be using humour during classes. The current research explores teacher-initiated humour in Academic English classes at Westminster International University in Tashkent and its effects on students. Besides, it seeks answers to questions as to what types of humour teachers employ during the class mostly, how often they use humour, as well as students’ and teachers’ recommendations given on how to use humour in class. This study uses both qualitative and quantitative data extraction methods in the form of an online questionnaire with students and a semi-structured interview with teachers. Obtained results show that affective and social roles of humour, its quality of lessening anxiety, creates favourable conditions for students and teacher’s connectedness, which outweighs other humour’s roles. Besides, mnemonic and engaging roles of humour received a solid support in the respondents. To obtain a more positive effect, it is recommended that teachers, when incorporating humour in class, apply a systematic approach. Humour should be planned beforehand and needs to be appropriate. Moreover, it should be used with moderation.